Defining and redefining harm reduction in the Lao context - Sychareun Vanphanom; Hansana Visanou; Phommachanh Sysavanh; Somphet Vathsana; Phommavongsa Phouthong; Tenni Brigitte; Moore Timothy; Crofts Nick (BMC, 2012)
Abstract The response to drug use in Laos has focused on reducing opium supply (supply reduction) and rates of drug use (demand reduction). However, recently there is increased interest among government counterparts to discuss and develop broader responses to injecting drug use (IDU) including the introduction of harm reduction programs. The concept of harm reduction has just been introduced to Lao PDR and as yet there is no agreement on a definition of the concept. We highlight here a range of issues that remain controversial in Lao PDR in the HIV, drug use and harm reduction discourse, the definition of 'harm reduction' and related terms; and the scope of harm reduction. This was a qualitative study, consisting of in-depth interviews with 27 law enforcement and 8 health officers who work in the fields of HIV and/or drug control about their understanding of HIV related to drug use, and concepts of harm reduction. Content analysis was performed to identify the coding, categories and themes. We found that law enforcement officers in particular had limited understanding about harm reduction and the feasibility and appropriateness of harm reduction services in the Lao context. Harm reduction should be a core element of a public health response to HIV where drug use and IDU exists. Recommendations include the necessity of increasing the awareness of harm reduction among law enforcement officers and providing appropriate evidence to support the needs of harm reduction policy and programs. HIV prevention and treatment strategies should be integrated within existing social and cultural frameworks, working with the task force for HIV/IDU and other government counterparts.